STUDY ON THE PRAWNS OF ASHTAMUDI BACKWATERS IN KERALA WITH SPECIAL REFERENCE TO PENAEIDS - Suseelan, C; Kathirvel, M (Indian Journal of Fisheries, 2011)
Fifteen species of prawns were recorded from Ashtamudi backwater system whicli included one species of sergesitid, five species of carideans and nine species of penaeids. The penaeid prawns were chiefly represented by juveniles of Penaeus semisulcatus, P., indicus, P. latisulcatus, Melapenaeus dobsoni and M. monoceros. While M dobsoni and P. indicus were the dominant species in most parts of the backwaters, P. semisulcatus occurred more abundantly in some of the deeper areas having relatively higher salinities (9.42-32.11% ). P. latisulcatus formed one of the common components of the catches taken during the post-monsoon period. Parapenaeopsis styltfera, the most dominant sepcies contributing to the marine fishery of this area, was encountered only in stray numbers. Commercial exploitation and population characteristics of the juvenile penaeid prawns in these nursery areas are briefly discussed